2004
DOI: 10.2527/2004.82102919x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term early gestational exposure to endophyte-infected tall fescue diets on plasma 3,4-dihydroxyphenyl acetic acid and fetal development in mares1,2

Abstract: Consumption of wild-type (toxic) endophyte-infected tall fescue (E+) by horses during late gestation is known to adversely affect pregnancy outcome; however, little is known of the potential disruptive consequences of E+ consumption by mares during the critical phases of placentation and fetal development in early pregnancy. The objective of this study was to evaluate the detrimental effects of feeding E+ to mares during early gestation. Mares (n = 12) paired by stage of gestation (d 65 to 100) were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…The steers were maintained on their respective pastures for 28 days. At baseline (time 0), 1, 2, 14, and 28 days post pasture assignment, plasma and urine were collected and processed for HRM (Li et al, 2013;Patel et al, 2015), urinary ergot alkaloid analysis (Hill et al, 2000), and plasma and urine catecholamine analysis (Smith et al, 2013;Youngblood et al, 2004). Additional details of these analyses are provided below.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The steers were maintained on their respective pastures for 28 days. At baseline (time 0), 1, 2, 14, and 28 days post pasture assignment, plasma and urine were collected and processed for HRM (Li et al, 2013;Patel et al, 2015), urinary ergot alkaloid analysis (Hill et al, 2000), and plasma and urine catecholamine analysis (Smith et al, 2013;Youngblood et al, 2004). Additional details of these analyses are provided below.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Thus, EA can potentially decrease appetite and food intake through modulation of the hypothalamic serotonergic tone (Rossi-Fanelli and Cangiano, 1991). Sheep plasma DA levels M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 increase (Henson et al, 1987) and plasma 3,4-dihydroxyphenyl acetic acid (DOPAC; a dopamine metabolite) levels in mares decrease (Youngblood et al, 2004) in response to toxic fescue consumption.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations
“…One study noted increased early equine embryonic mortality with exposure to E fescue (Brendemuehl et al, 1994), and depressed endogenous catecholamine activity has been observed in mares exposed to E fescue early in gestation (Youngblood et al, 2004). However, other studies have found no increased equine pregnancy loss up to day 300, despite lower progestagen concentrations between gestational days 90 and 120 (Brendemuehl et al, 1996).…”
Section: Subfertilitymentioning
confidence: 95%